Gambaran Kestabilan Suhu Tubuh Bayi Baru Lahir Yang Dilakukan Inisisasi Menyusui Dini (IMD) di Ruang Bayi RSU Bahagia Makassar - Muhammad Sofyan; Sainah Sainah; Surmayanti Surmayanti (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Hypotermia is a condition in wich the body experiences a decrease in core temperature (body temperature <36,5°C). One simple intervention to keep the baby’s temperature stable is Early Breastfeeding  Initiation (EBI). The aim of this study to determine the difference of axillary temperature of newborn between improper EBI group and proper EBI group for 24 hours in RSU Bahagia Makassar. This prospective cohort study was conducted at Aisyiyah Muntilan Hospital. Sixty-two healthy newborns from healthy mothers born in November 2016 who meet the inclusion and exclusion criteria. Subjects were grouped in improper EBI groups (n=32) and proper EBI groups (n=32). Axila temperature measurements were performed at 1st minute, 30th minute, 60th minute, 6th hour, 12th hour, 24th hour. The result of the hypotermic occurrence is more happened on improper EBI than proper EBI. EBI is able to prevent hypothermia during the first 24 hours of newborn life. Infants with proper EBI have a lower risk of hypothermia